A new model for the pathozone of the take‐all pathogen, Gaeumannomyces graminis var. tritici. (23rd August 2013) - Gosme, M.; Lebreton, L.; Sarniguet, A.; Lucas, P.; Gilligan, C.A.; Bailey, D.J.
Abstract The pathozone (volume of soil surrounding subterranean plant organs within which a propagule must occur if it is to have any chance of infecting the organ) is usually described by statistical models lacking biological meaning. For this reason, pathozone results might be difficult to interpret and the estimated parameters cannot be re‐used in other studies. We developed a model with parameters reflecting life‐history traits concerning primary infections of soilborne pathogens. The model was then fitted to experimental data obtained from eight isolates of Gaeumannomyces graminis var. tritici, causal agent of take‐all disease of wheat. Our model provided not only a mechanistic description for the pathozone dynamics, but also a better fit to the data than four other models published in the literature. Although the isolates displayed phenotypic variability in terms of pathozone dynamics, these differences did not map onto the G1 and G2 genetic subgroups known to occur in Ggt populations.